The Contribution of Non-Malay Architects To The Development of National Architecture Identity in Malaysia - Bahari, Ashran; Sabil, Azmal; Yusof, Hanita; Hamzah, Mohammad Hazazi; Ismail Jamail, Maliza (International Journal of Integrated Engineering, 2023)
The idea of adapting Malay traditional architectural values has been gazetted as one of the resolutions for National Architecture Identity as presented in ‘Seminar Ke Arah Identiti Kebangsaan Dalam Seni Bina’ in 1981. The resolution heavily influenced the adaptation of traditional Malay architecture, motives, and artefact onto modern architecture as a form to inculcate a singular and united national identity. A lot of research and documentation on good and meaningful architecture embracing the ideals of National architecture identity through the worldview and perspectives of Malay scholars and architects have been documented through books, journals, magazines and extensively discussed during seminars, symposiums, and discourses. Ironically, the contributions of Non-Malay architects adapting Malay symbolism to enunciate or articulate national pride and identity, either due to policies or interest, are minimally discussed and highlighted. This publication attempted to document the contributions of non-Malay architects to the national architecture identity construct. It is crucial to shape future philosophies, theories, criticisms, and thoughts on the overall built environment in developing a comprehensive construct of national architectural identity that does not necessarily rely on ethnocentric criteria based on a single race dominance. The research allows us to expand and progress the local architecture narrative by including diverse voices and thoughts, especially of those who have contributed extensively in the eras of nation-building. This inclusive and diverse input will, in turn, inform and expand the discourse of national identity and unity.